WORKSHOP MELUKIS PADA KALENG BEKAS UNTUK SMAN 2 SURAKARTA - Syamsiar Syamsiar (Abdi Seni, 2016)
Devotion to Society with the program of workshop â€œMelukis pada Wadah Kaleng Bekasâ€ (Drawing at the Used Cans) is supposed to gain the participantsâ€™ potency in artistic sensitivity. It also aims to make young generation moreÂ  love their culture.Â  In the workshop, students are leaded to create a work of cans painting with the theme of their surrounding culture such asÂ batik,Â wayangÂ characters, and so on. Devotion to Society aims toÂ  increase the appreciation and ability in drawing at the used cans for students in SMAN 2 Surakarta. The program is executed using the method of speech and discussion as well as workshop on introducing directly to drawing method and instruments. This is supposed to make students able to draw at the cans well and make them realize about their environment hygiene.Key wordsÂ :Â drawing, workshop.